The Fear of Marriage in Islamic Legal Perspective: Religious Scholars’ Views on Unmarried Individuals in Asahan Regency - Antika, Ade Sri; Mukhsin , Abd. (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study aims to explore the factors influencing individuals to choose not to marry and examine the perspectives of religious scholars in Asahan Regency regarding this decision. Employing an empirical approach with a sociological legal framework, this research utilizes a qualitative descriptive method. Primary data were collected through in-depth interviews with eight residents of Sei Renggas and five religious scholars in Asahan Regency, while secondary data were sourced from journals and relevant literature. The findings reveal that the decision to remain unmarried is primarily driven by fear, stemming from past relationship trauma, economic constraints, aspirations for career advancement or further education, and adverse family experiences. From an Islamic legal perspective, postponing marriage for economic reasons is permissible, as marriage law is contextualized based on individual circumstances. This study provides a nuanced understanding of the fear of marriage phenomenon within a specific socio-religious context. It highlights the interplay between personal, economic, and cultural factors in shaping marital decisions and contributes to the discourse on religious scholars’ roles in addressing such concerns. Addressing the fear of marriage in Asahan Regency requires a collaborative effort. Policymakers should develop marriage education programs that emphasize mental, economic, and social preparedness while expanding access to premarital counseling. Religious scholars must offer balanced guidance on marriage rulings, providing appropriate solutions for those hesitant to marry. Additionally, the community should foster a supportive environment by reducing the stigma against unmarried individuals and promoting open family communication to prevent intergenerational trauma. A coordinated approach among the government, religious scholars, and society is essential to fostering a more informed and constructive discourse on marriage.